COMMERCIAL LAW IN MALAYSIA THEORIES AND PRINCIPLES - Nor 'Adha Abdul Hamid; Surianom Miskam (Centre of Research and Development, Kolej Universiti Islam Antarabangsa Selangor, 2009)
This book introduces the concepts and basic principles related to commercial law in Malaysia. It is meant to provide simple guide to those interested in this area and to those concerned with its study especially the readers and students in business management, accountancy, law and other related fields.